2018
DOI: 10.1029/2018gl077736
|View full text |Cite
|
Sign up to set email alerts
|

Low Phosphorus Availability Decreases Susceptibility of Tropical Primary Productivity to Droughts

Abstract: Large uncertainties in the susceptibility of tropical forest productivity to precipitation changes hamper climate change projection. Interactions between the availabilities of water and phosphorus could theoretically either increase or decrease the susceptibility of tropical gas exchange to variation of precipitation. The inclusion of phosphorus‐water interactions in a land surface model reduces the coefficient of variance, a measure of variability, of biweekly gross primary productivity by a factor of 1.5–2.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 78 publications
(121 reference statements)
0
20
0
Order By: Relevance
“…Previous studies have reported that the lack of dynamic root growth, hydrological redistribution, groundwater movement, and reasonable carbon allocation during droughts in models are potential causes responsible for larger estimation of vegetation response to water deficit (Hu et al, ; Li et al, ; Paschalis et al, ). For example, during Amazon droughts, trees can increase water use efficiency and uptake water from aquifer through deep roots to mitigate drought impacts (Goll et al, ; Yang et al, ). Thus, vegetation adaption strategies and more sophisticated hydrological processes need to be taken into consideration by TBMs to improve the simulation accuracy of the changed carbon flux during drought events.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the lack of dynamic root growth, hydrological redistribution, groundwater movement, and reasonable carbon allocation during droughts in models are potential causes responsible for larger estimation of vegetation response to water deficit (Hu et al, ; Li et al, ; Paschalis et al, ). For example, during Amazon droughts, trees can increase water use efficiency and uptake water from aquifer through deep roots to mitigate drought impacts (Goll et al, ; Yang et al, ). Thus, vegetation adaption strategies and more sophisticated hydrological processes need to be taken into consideration by TBMs to improve the simulation accuracy of the changed carbon flux during drought events.…”
Section: Discussionmentioning
confidence: 99%
“…8). The higher flux in the pCO 2 -based flux products than in the ocean models might be explained by a known lack of surface ocean pCO 2 observations in winter, when CO 2 outgassing occurs south of the Polar Front (Gray et al, 2018).…”
Section: Regional Distributionmentioning
confidence: 93%
“…But most importantly, our result under RCP6.0 reveals that CO 2 effect on carbon sink would saturate, suggesting the negative feedback of terrestrial ecosystems to climate warming has its upper threshold. In addition, the CO 2 -caused carbon sink may be further limited by nutrient availability, such as nitrogen limitation in high latitudes (Du et al, 2020; Y. P. Wang et al, 2011) and phosphorous in tropical regions (Du et al, 2020;Goll et al, 2018;Y. P. Wang et al, 2011).…”
Section: Co 2 -Caused Carbon Sinkmentioning
confidence: 99%